The Effect of The Use of Birthball on The Intensity of First Stage Active Phase Labor Pain - Bunga Tiara Carolin; Andi Julia Rifiana; Dedeh Komariah (Health and Technology Journal (HTechJ), 2023)
Research in the United States around 70% to 80% of mothers who give birth expect the birth to take place without feeling pain. Currently, 20% to 50% of deliveries in private hospitals in Indonesia are carried out by Caesarean section. The current trend is for mothers to choose to give birth via cesarean section to avoid pain during normal birth. This study was to determine the effect of using a birthball on the intensity of labor pain during the first active phase. This type of research is quasi-experimental with a pretest-posttest two-group design. The population of this study is all mothers giving birth normally at the Az-Zahra clinic. The sample in the study consisted of 30 respondents. The research instrument uses the Numeric Rating Scale (NRS) sheet. Data were analyzed using the Paired T-test and Independent T-test. The average pretest labor pain score in the experimental group was 7.13, while the post-test was 3.33, and the p-value was 0.489. The average pretest labor pain score in the control group was 6.53, while the post-test was 7.80, and the p-value was 0.044. The results of the Independent T-test showed a p-value of 0.489. Giving the Birthball method can reduce the intensity of labor pain during the first active phase. It is hoped that the Birthball method can be applied in all maternity clinics or independent midwives in Indonesia.